THE EFFECT OF WORK ENVIRONMENT AND MOTIVATION ON JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT AND THEIR IMPACT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOUR - Joko Kurniawan; Budi Eko Soetjipto; Agus Hermawan (Journal of Management and Informatics, 2022)
This study aims to determine the role of work environment, motivation, job satisfaction, and organizational commitment in improving the Organizational Citizenship Behavior (OCB) for the employee at the PT Garudafood Putra Putri Jaya Tbk of Gresik area. The research method applied is quantitative, using path analysis and the Sobel test to examine the relationship and the magnitude of the contribution of influence between each variable. The number of respondents in this study was 200 employees.The results showed that the work environment and motivation significantly positively affected job satisfaction. Meanwhile, work environment, motivation, and job satisfaction positively and significantly affect organizational commitment. It was found that communication between superiors and subordinates is an essential factor for improving OCB, so further research is needed on the effect of leadership style on OCB